Analysing the value of environmental citizen-generated data: Complementarity and cost per observation. (1st February 2022) - Alfonso, Leonardo; Gharesifard, Mohammad; Wehn, Uta
Abstract: The proliferation of Citizen Science initiatives has increased the expectations of practitioners who need data for design, analysis, management and research in environmental applications. Many Citizen Science experiences have reported tangible societal benefits related to improved governance of natural resources due to the involvement of citizens and communities. However, from the perspective of data generation, most of the literature on Citizen Science tends to regard it as a potentially cost-effective source of data, with major concerns about the quality of data. The Ground Truth 2.0 project brought the opportunity to examine the scope of this potential by analysing the value of citizen-generated data. We propose a methodology to account for the value of citizen observations as a function of their complementarity to existing environmental observations and the evolution of their costs in time. The application of the proposed methodology in the chosen case studies that were all established using a co-design approach shows that the cost of obtaining Citizen Science data is not as low as frequently stated in literature. This is because the costs associated with co-design events for creating a Citizen Science community, as well as the functional and technical design of the tools, are much higher than the costs of rolling out the actual observation campaigns. In none of the considered cases did an increment in the number of preparatory events translate into an immediate increase in the collected observations. Nevertheless, Citizen Science appears to have the greatest value in places where in-situ environmental monitoring is not implemented. Highlights: Recent literature claims that Citizen Science is a low-cost, gap-filling data source. A method to evaluate these claims is proposed, using objective, explicit indicators. Four real case studies aiming to collect environmental data were analysed. Citizen observations filled 0–40% of the data gaps, at 37 to 300 Eur per observation. Co-designing Citizen Science projects exclusively aimed at data collection might not be worthwhile.